El más allá al final del camino. De Chrétien de Troyes y Montalvo a Conrad y Céline - Carmona Fernández, Fernando (Revista de Filología Románica, 2006)
Knight’s travel, following the Chrétien de Troyes model, culminates and comes to an end with the adventure in an extraordinary space and facing supernatural creatures. This kind of adventure, that typifies the two most representative Chrétien’s romans (Erec et Enid and Yvain), will be reproduced with accuracy at the end of the First Book of the Amadís. The African journeys of the J. Conrad’s (Heart of Darkness, 1902) and Céline’s characters (Voyage au bout de la nuit, 1932) reproduce the model of the voyage to the underworld of the mentioned medieval texts, with the same features.